Protocolos hormonais de preparação de doadoras bovinas para produção de embriões in vitro - Miyauchi, Tatimara Maria (2011)
Efficiency of in vitro bovine embryo production has been affected by low quantity and quality of recovered oocytes from ultrasound-guided follicular aspiration (OPU). The objective of this study was to evaluate the effect of different synchronization of follicular wave protocols in the production of oocytes and embryos in vitro, of Bos taurus taurus and Bos taurus indicus and heifers. We used three hundred forty-four results of follicular aspiration. The management regime was semi- confinement of animals with positive energy balance ten days prior to the aspirations. Animals were randomly distributed in the following treatments: TI or control (N=81) - OPU independent of estrous cycle with no previous hormone treatment; TII (N=97) - Estradiol benzoate (3mg), four days before OPU; TIII (N= 97) - Estradiol benzoate (3mg), insertion of subcutaneous implant of Norgestomed and application of D-Chloprostenol Sodium (0.150 mg), four days before OPU; TIV (N= 69) the same treatment used in TIII, plus two doses of FSH (100 to 150 UI) one day before OPU, with an interval of 12 hours, OPU after 12 to 16 hours. Viable recovered oocytes were in vitro matured, fertilized and cultured and presumptive zygotes were cultured until the time of embryo transfer. Zebu showed greater recovery of viable oocytes and total production of embryos in relation to taurine respectively (14.2± 0.7 vs 8.8± 0.5; 17.7± 0.9 vs 11.9± 0.6; 4.3± 0.3 vs 2.1± 0.2). A significant increase in quality and oocyte recovery in groups III and IV in relation to control group, respectively (13.2± 1.0 vs 13.8± 1.1 vs 8.1± 0.8; 16.8± 1.2 vs 17.8± 1.4 vs 10.7± 1.0 , P <0.05). In relation to the total quantity and quality of embryos, all treatments were superior to control (P <0.05), but T IV was superior to other treatments according to the breeds studied. Treatments III and IV showed a greater recovered oocyte number in Bos taurus; the same was not observed in Zebu. A better average conversion was observed in Zebu cows. Bos indicus presented greater quality and recover rate of oocytes in summer compared to winter (15.7± 1.6 vs 12.0± 1.0; 19.3± 1.3 vs 15.3± 1.2). Bos indicus produced more embryos in both seasons and, in winter, both subspecies converted more oocytes into embryos compared with to summer (41.5± 3.5 vs 33.1± 2.4; 28.5± 3.2 vs 19.5± 2.6). Synchronization treatments were efficient in oocyte recovering of Bos taurus donors and Bos indicus embryos. Regarding the season of the year, winter has proved to be the most favorable period for conversion of embryos for the two subspecies.